Поширення видів роду Pedicularis (Orobanchaceae) в Україні - Перегрим, О.М.; Перегрим, М.М. (Український ботанічний журнал, 2014)
Анализируется хорология 10 видов рода Pedicularis L. флоры Украины. Рассматривается ареал каждого вида и особенности его географического распространения в стране. На территории Украины проведены условные линии границ распространения 6 видов. Chorology of 10 species of Pedicularis L. in the Ukrainian flora is analyzed and generalized. The ranges of each species and descriptions of geographical distribution in Ukraine are provided. For 6 species, their distribution boundaries in Ukraine are delineated.